Taurine Promotes Neurite Outgrowth and Synapse Development of Both Vertebrate and Invertebrate Central Neurons - Mersman, Brittany; Zaidi, Wali; Syed, Naweed I.; Xu, Fenglian (Frontiers in Synaptic Neuroscience, 2020)
Taurine is a sulfur-containing amino acid that is widely expressed throughout the human brain, heart, retina, and muscle tissues. Taurine deficiency is associated with cardiomyopathy, renal dysfunction, abnormalities of the developing nervous system, and epilepsy which suggests a role specific to excitable tissues. Like vertebrates, invertebrates maintain high levels of taurine during embryonic and larval development, which decline during aging, indicating a potential developmental role. Notwithstanding its extensive presence throughout, taurine’s precise role/s during early brain development, function, and repair remains largely unknown in both vertebrate and invertebrate. Here, we investigated whether taurine affects neurite outgrowth, synapse formation, and synaptic transmission between postnatal day 0 rat cortical neurons in vitro, whereas its synaptogenic role was tested more directly using the Lymnaea soma-soma synapse model. We provide direct evidence that when applied at physiological concentrations, taurine exerts a significant neurotrophic effect on neuritic outgrowth and thickness of neurites as well as the expression of synaptic puncta as revealed by immunostaining of presynaptic synaptophysin and postsynaptic PSD95 proteins in rat cortical neurons, indicating direct involvement in synapse development. To demonstrate taurine’s direct effects on neurons in the absence of glia and other confounding factors, we next exploited individually identified pre- and postsynaptic neurons from the mollusk Lymnaea stagnalis. We found that taurine increased both the incidence of synapse formation (percent of cells that form synapses) and the efficacy of synaptic transmission between the paired neurons. This effect was comparable, but not additive, to Lymnaea trophic factor induced synaptogenesis. This study thus provides direct morphological and functional evidence that taurine plays an important role in neurite outgrowth, synaptogenesis, and synaptic transmission during the early stages of brain development and that this role is conserved across both vertebrate and invertebrate species.